Review paperThe influence of selected ingredients of dietary supplements on skin condition - Szyszkowska, Barbara; Łepecka-Klusek, Celina; Kozłowicz, Katarzyna; Jazienicka, Iwona; Krasowska, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction and aim of the article. Healthy skin is an excellent barrier maintaining balance between the internal and external environment of the body. Because it is constantly changing as a result of, on the one hand, environmental factors and, on the other hand, the process associated with skin aging, it requires many nutrients and minerals that help maintain its homeostasis. The aim of this dissertation is to discuss the most commonly used ingredients in dietary supplements that improve the appearance and quality of the skin. Brief description of the state of the art. Quick pace of life, unbalanced diet and stress make it impossible to provide all the necessary components, which affects the proper functioning of the skin. That is why, the interest in dietary supplements as products that help to reduce the deficiencies of individual components is increasing. Supplements that affect the skin, hair and nails mainly consist of: vitamins C, E, A, B-vitamins, micro- and macronutrients and fatty acids. In this paper, some of the ingredients of skin affecting dietary supplements are discussed. A varied and proper diet should provide all the nutrients necessary for the correct functioning of the body. Dietary supplements are intended to supplement the normal daily food intake of nutrients which are not supplied with food in a sufficient quantity. Therefore, their use becomes relevant.